1975
DOI: 10.1677/joe.0.0640549
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Daylength and Level of Feeding on Serum Prolactin in Growing Lambs

Abstract: Twenty-four castrated male lambs initially maintained on a photoperiod of 12 h light:12 h dark were allocated to a factorial experiment with two daylengths (8 h L: 16 h D or 16 h L: 8 h D) and two levels of feeding (restricted or ad libitum). Blood samples were taken every 4 h for 24 h during the introductory period and after 24, 51 and 79 days of treatment. There were highly significant positive effects of daylength and level of feeding on serum prolactin: mean concentrations increased from a mean of 38 plus … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

9
26
0
3

Year Published

1978
1978
2015
2015

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 69 publications
(38 citation statements)
references
References 0 publications
9
26
0
3
Order By: Relevance
“…In our experiment, ghrelin increased PRL secretion in fasted ewes during LD but decreased PRL production in fasted and non-fasted sheep during the SD period. In addition, ghrelin significantly augmented PRL secretion during the LD season in normally fed animals, thereby indicating that the effects of ghrelin on PRL secretion are both season-and nutrition-dependent, as previously postulated by Forbes et al [29] based on a study in growing lambs. Garin et al [30] suggested that ghrelin inhibits PRL secretion in rodents by elevating the serotonergic tone.…”
Section: Discussionsupporting
confidence: 76%
“…In our experiment, ghrelin increased PRL secretion in fasted ewes during LD but decreased PRL production in fasted and non-fasted sheep during the SD period. In addition, ghrelin significantly augmented PRL secretion during the LD season in normally fed animals, thereby indicating that the effects of ghrelin on PRL secretion are both season-and nutrition-dependent, as previously postulated by Forbes et al [29] based on a study in growing lambs. Garin et al [30] suggested that ghrelin inhibits PRL secretion in rodents by elevating the serotonergic tone.…”
Section: Discussionsupporting
confidence: 76%
“…Thus, prolactin administration can lead to increased weight gain in female rats [2], to in creased protein synthesis in rat adipose tissue [20], to bone growth in hypophysectomized rats [39], and to the growth of lean body mass in sheep [36]. Serum prolactin concentration is positively correlated with the rate of weight gain in wo men with anorexia nervosa [3,22], in lambs [14], and in bull calves [8,24,33,36]. Prolactin may account for the high food consumption in the lactating rat as its pharmacologi cal suppression inhibits food intake [11,18,40], and admin istration of prolactin to nonlactating rats induces increased food intake and weight gain [25,26].…”
Section: Discussionmentioning
confidence: 99%
“…INTRODUCTION The plasma concentrations of a number of hormones, including prolactin, cortisol and testosterone, have been shown to be dependent on the length of the daily photoperiod, with higher concentrations at certain times of the year or with different photoperiodic lengths. The plasma levels of prolactin in sheep are found to be higher in summer than in winter (Ravault, 1976;Kay, 1979) and in photoperiods of 16 h light per day compared with 8 h light per day (Forbes, Driver, El Shahat et al 1975;Brown & Forbes, 1980;Lincoln & Short, 1980;Lincoln, Almeida, Klandorf & Cunningham, 1982). It has also been shown that pro¬ lactin is affected similarly by photoperiods of 16 h light and skeleton long photoperiods (7 h light : 9 h darkness: Ih light : 7 h darkness (7L:9D: IL: 7D), Ravault & Ortavant, 1977 Photoperiodic effects on cortisol have not been detected by several authors (Peters, Chapin, Emery & Tucker, 1980;Kennaway, Obst, Dunstan & Friesen, 1981;Lincoln et al 1982) though one report with prepubertal bulls (Leining, Tucker & Kesner, 1980) has shown a reduction in plasma cortisol levels in long photoperiods when compared with short photo¬ periods.…”
mentioning
confidence: 99%